Republic of Mozambique : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2011)
The Poverty Reduction Action Plan (PARP) 2011-14 is the medium-term strategy of the Government of Mozambique for putting into operation the Five-Year Government Program (2010-14). This medium-term instrument is part of the National Planning System (SNP) and is aligned with the vision of Agenda 2025. To achieve the objective of inclusive economic growth for reducing poverty, the government has defined general objectives, to which government efforts will be directed. The PARP is a dynamic and flexible instrument.